Association of inflammatory, lipid and mineral markers with cardiac calcification in older adults. - Bortnick, Anna E; Bartz, Traci M; Ix, Joachim H; Chonchol, Michel; Reiner, Alexander; Cushman, Mary; Owens, David; Barasch, Eddy; Siscovick, David S; Gottdiener, John S; Kizer, Jorge R (Heart, 2016)
OBJECTIVE: Calcification of the aortic valve and adjacent structures involves inflammatory, lipid and mineral metabolism pathways. We hypothesised that circulating biomarkers reflecting these pathways are associated with cardiac calcification in older adults. METHODS: We investigated the associations of various biomarkers with valvular and annular calcification in the Cardiovascular Health Study. Of the 5888 participants, up to 3585 were eligible after exclusions for missing biomarker, covariate or echocardiographic data. We evaluated analytes reflecting lipid (lipoprotein (Lp) (a), Lp-associated phospholipase A2 (LpPLA2) mass and activity), inflammatory (interleukin-6, soluble (s) CD14) and mineral metabolism (fetuin-A, fibroblast growth factor (FGF)-23) pathways that were measured within 5 years of echocardiography. The relationships of plasma biomarkers with aortic valve calcification (AVC), aortic annular calcification (AAC) and mitral annular calcification (MAC) were assessed with relative risk (RR) regression. RESULTS: Calcification was prevalent: AVC 59%, AAC 45% and MAC 41%. After adjustment, Lp(a), LpPLA2 mass and activity and sCD14 were positively associated with AVC. RRs for AVC per SD (95% CI) were as follows: Lp(a), 1.051 (1.022 to 1.081); LpPLA2 mass, 1.036 (1.006 to 1.066) and LpPLA2 activity, 1.037 (1.004 to 1.071); sCD14, 1.039 (1.005 to 1.073). FGF-23 was positively associated with MAC, 1.040 (1.004 to 1.078) and fetuin-A was negatively associated, 0.949 (0.911 to 0.989). No biomarkers were significantly associated with AAC. CONCLUSION: This study shows novel associations of circulating FGF-23 and fetuin-A with MAC, and LpPLA2 and sCD14 with AVC, confirming that previously reported for Lp(a). Further investigation of Lp and inflammatory pathways may provide added insight into the aetiology of AVC, while study of phosphate regulation may illuminate the pathogenesis of MAC.